Anatomical Considerations of Costal Abnormalities with its Clinical Significance - B. F. Jazeela; Meera Jacob; Ashwini Shetty (Archives of Medicine and Health Sciences)
Synostosis is an immobile joint created by the ossification of two bones. About 0.3% of ribs have synostosis, an unexpected radiographic finding. The present study aims to detail every instance of rib synostosis and provide an overview of its evolutionary, morphological, and clinical significance for anatomists, radiologists, and surgeons. Four hundred dry specimens of adult ribs of anonymous sex and origin in the Yenepoya Medical College, Department of Anatomy’s osteological collections, were subject to the current investigation. In addition to one forked and bridged rib and two occurrences of costovertebral synostosis, we discovered five examples of manubriocostal synostosis. All synostotic bones underwent morphological analysis, and measurements were taken using vernier calipers. There is limited research on rib abnormalities in clinical medicine. Clinicians and radiologists must be conversant with how these variances look on imaging. These anomalies highlight the early organogenesis changes that may be associated with stillbirths, cancer, and other defects.